+0  
 
0
66
1
avatar

Give two different decompositions of the following functions into two new functions, u and v, where v is the inside function and 𝑒(π‘₯) β‰  π‘₯ and 𝑣(π‘₯) β‰  π‘₯. Verify that 𝑓(π‘₯) = 𝑒(𝑣(π‘₯)) in each case.

 

 Feb 12, 2020
 #1
avatar+109740 
+1

a.   

Let  u(x)  =   βˆ› x

Let v (x) =  1 - 4ex

Then   u ( v(x) )   means that we are subbing  v  into the "x" in   u    =    βˆ›[ 1 - 4ex ]   =  f(x) 

 

b. This one is a little tricky   .....

 

Let  u(x)  =    1 + x

                     ______

                      2 + x

 

Let v (x)  =   x^2

 

                                    1  + x^2

So... u(v (x))   =           _________  =   f(x) 

                                    2  +  x^2

 

c.

Let u(x)  =  ln (x)

Let v(x)  =  2 -  1/x

Then   u (v(x))  =  ln ( 2 - 1/x)  =  f(x)

 

 

cool cool cool

 Feb 12, 2020

47 Online Users

avatar
avatar
avatar
avatar
avatar
avatar